Contemporary Oral Oncology : Oral and Maxillofacial Reconstructive Surgery - Kuriakose, Moni Abraham (Springer International Publishing : Imprint: Springer, 2017)
This is the third of four volumes that together offer an authoritative, in-depth reference guide covering all aspects of the management of oral cancer from a multidisciplinary perspective and on the basis of a strong scientific foundation. This volume is devoted to the reconstructive surgical techniques used in patients with oral cancer. Following introductory chapters outlining the general principles of reconstructive surgery in the oral cavity and the planning of maxillofacial reconstruction, detailed descriptions of the options and techniques employed in reconstruction of each of the functional subunits are provided. Important technologic advances are also discussed, including image-guided surgery, robotic surgery, and tissue-engineered and prefabricated approaches. Finally, the current status of facial transplantation for maxillofacial reconstruction is reviewed. This volume is intended for both trainees and practicing surgeons.
Keywords: Dentistry.; Medicine.; Oncology.; Oral surgery.; Maxillofacial surgery.; Surgical oncology.; elektronické knihy; electronic books